2001
DOI: 10.1111/j.1469-7793.2001.0467f.x
|View full text |Cite
|
Sign up to set email alerts
|

Microdialysis perfusion of 5‐HT into hypoglossal motor nucleus differentially modulates genioglossus activity across natural sleep‐wake states in rats

Abstract: The genioglossus (GG) muscle of the tongue contributes to effective lung ventilation by maintaining an open pharyngeal airway. Decreased GG activity in sleep, especially REM sleep (Sauerland & Harper, 1976) can lead to airway narrowing, increased upper airway resistance and hypoventilation (Henke et al. 1992). In individuals with already anatomically narrow upper airways, such GG suppression can produce airway occlusion and obstructive sleep apnoea (Remmers et al. 1978), a serious sleep-related breathing disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
173
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(192 citation statements)
references
References 44 publications
18
173
1
Order By: Relevance
“…Our previous study showed a reduction of norepinephrine and serotonin release in both the spinal ventral horn and hypoglossal (XII) nucleus during PIA stimulation in the decerebrate cat (Lai et al, 2001). This result combined with other studies that showed a facilitatory effect of these monoamines on motoneurons (Takahashi and Berger, 1990;Parkis et al, 1995;Jelev et al, 2001) indicates that disfacilitation plays an important role in muscle tone suppression.…”
Section: Introductionsupporting
confidence: 57%
“…Our previous study showed a reduction of norepinephrine and serotonin release in both the spinal ventral horn and hypoglossal (XII) nucleus during PIA stimulation in the decerebrate cat (Lai et al, 2001). This result combined with other studies that showed a facilitatory effect of these monoamines on motoneurons (Takahashi and Berger, 1990;Parkis et al, 1995;Jelev et al, 2001) indicates that disfacilitation plays an important role in muscle tone suppression.…”
Section: Introductionsupporting
confidence: 57%
“…It was not until 2001 that the central neurotransmitter systems underlying the modulation of a respiratory motoneuron pool began to be investigated across states of wakefulness and natural sleep following the development of appropriate freely behaving animal models (Jelev et al 2001). Studies using such a model were initially focused on the hypoglossal motor nucleus, as illustrated in figure 3.…”
Section: Model System To Determine Mechanisms Underlying Sleep-wake-dmentioning
confidence: 99%
“…Changes in the serotonergic system have been implied in several human diseases such as depression, headaches, epilepsy, obsessive-compulsive behaviors, temporomandibular dysfunction, and affective disorders. [6][7][8][9] Serotonin also has a relevant role in upper airway patency, as it excites airway motor neurons and intrinsically excites the motor neurons in the brainstem. The activity of neurons that provide 5-HT to motor neurons declines with sleep; most of the functional studies have shown that 5-HT and serotonergic neurons exert a significant excitatory effect on respiratory motor neurons in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…6 The genioglossus muscle is innervated by neurons that originate in the hypoglossal nucleus within the brainstem; contractions of this muscle during inspiration help ventilate the lungs and keep upper airways open during wakefulness and sleep. 7,8 Groups of serotonergic and noradrenergic cells may generate parallel patterns by stimulating directly the motor cells of the hypoglossal nerve, thereby regulating these dilating muscles. Thus, activation of these cell groups increases the activity of the genioglossus muscle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation